Dead End at the Silk Road: The Possible Revival of the Banaras Handloom Industry - Agnihotri, Miheer Prafulla (Prabandhan: Indian Journal of Management, 2015)
An emerging market provides an ideal platform for a product or a sector to reinvent itself. The growth that is forecasted for the Indian textiles and garment market can be efficiently utilized by the handloom sector to come back from the cold and become a booming business once again. However, this largely unorganized sector needs active support from the state and the private players in terms of policy reforms and effective logistics management to get back on its feet once again. With the new government's chant of "Make in India," this study reflected the ground realities whilst making in India by shedding light on the grass root level hardships that the weavers of the Varanasi cluster face and went on to suggest certain policy level interventions for the development of the weaver community and the handloom sector as a whole. Furthermore, the paper highlighted how ineffective civic governance can have adverse effects on businesses as well.